Reputation, Identity, and Symbolic Defence: The Role of the Consumer in Digital Brand Crises – The Frisby Case - Amado Mateus, Marelby; Guzmán Rincón, Alfredo; Martín-Caro Álamo, Ester (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
In digital ecosystems, brand crises have become arenas for spontaneous consumer activism beyond corporate control. This study examines the emotional and symbolic responses of Instagram users to the trademark dispute between Frisby Colombia and a homonymous Spanish company. Drawing on emotional branding, national identity, and brand defence frameworks, a computational approach was adopted. A total of 4,067 public Instagram posts were collected, preprocessed, and analyzed using TF-IDF, sentiment analysis, and K-means clustering validated through PCA. Results show that collective mobilization was driven by emotional resonance and symbolic identification rather than corporate communication, highlighting the role of cultural identity and social listening in digital brand crisis management.